A Study of Gene Expression of Survivin, its Antiapoptotic Variants, and Targeting Survivin In Vitro for Therapy in Retinoblastoma. Issue 7 (October 2016) - Samuel, Jaisy; Kanwar, Rupinder K.; Kanwar, Jagat R.; Khetan, Vikas; Krishnakumar, Subramanian
Abstract : Apoptosis is a natural process regulated by apoptotic and antiapoptotic molecules. We investigated mRNA expression of survivin and its splice variants, along with B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (Bax), in a cohort of 20 retinoblastoma (RB) tumors by real-time polymerase chain reaction. We hypothesized a correlation between the Bcl-2/Bax and survivin splice variants and also that expression of these would be associated with clinicopathologic features of tumors. The Bcl-2 expression was significantly higher ( P <0.001) in RB, and Bcl-2/Bax ratio was remarkably higher in poorly differentiated tumors. A statistically significant higher expression of Survivin-WT (wild type) compared with its variant Survivin-2β ( P <0.05) was observed. Bcl-2 did not exhibit positive correlation with any of the survivin variants except Survivin-2β, whereas Bax exhibited significant ( P <0.05) correlation with the variants. Thus, it could be suggested that a superior player out of a likely interaction between the variants and Bcl-2/Bax uses its activity for the progression of RB. Silencing of Survivin-WT in the Y79 cell line was studied by siRNA technology and cell-permeable dominant negative survivin (SurR9-C84A). siRNA showed higher proapoptotic effects and increased caspase 3/7 activity in Y79 cells. Effective internalization of SurR9-C84A in Y79 cells induced cytotoxic effects. Thus, the current study confirms survivin as a promising target for therapy.